Management of pancreatogenic diabetes: challenges and solutions - Makuc J (Dove Medical Press, 2016)
Jana Makuc Department of Internal Medicine, General Hospital Slovenj Gradec, Slovenj Gradec, Slovenia Abstract: Pancreatogenic diabetes is an underdiagnosed form of secondary diabetes that is lacking official management guidelines. This paper reviews the recommended management strategies with additional data on the promising novel drugs. Keywords: T3cDM, pancreatogenic diabetes, diabetes management, brittle diabetes, hypoglycemia